2002
DOI: 10.1146/annurev.micro.56.012302.160950
|View full text |Cite
|
Sign up to set email alerts
|

The Class Mesomycetozoea: A Heterogeneous Group of Microorganisms at the Animal-Fungal Boundary

Abstract: When the enigmatic fish pathogen, the rosette agent, was first found to be closely related to the choanoflagellates, no one anticipated finding a new group of organisms. Subsequently, a new group of microorganisms at the boundary between animals and fungi was reported. Several microbes with similar phylogenetic backgrounds were soon added to the group. Interestingly, these microbes had been considered to be fungi or protists. This novel phylogenetic group has been referred to as the DRIP clade (an acronym of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
231
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(243 citation statements)
references
References 77 publications
8
231
0
4
Order By: Relevance
“…Therefore, it was not surprising that nSSU rDNA analyses (Benny and O'Donnell, 2000;Ustinova et al, 2000) indicated that Amoebidium was located within the DRIP's clade (an acronym of the organisms included in this clade: Dermocystidium, rosette agent, Ichthyophonus, and Psorospermium), a recently proposed clade near the Animal-Fungi divergence (Ragan et al, 1996). The DRIP's clade was identified as a novel class Mesomycetozoea (Herr et al, 1999;Mendoza et al, 2002). Specifically, the nSSU rDNA data suggests that the closest relative of Amoebidium is the fish pathogen Ichthyophonus, but a specific phenetic connection between these two organisms has not been discovered.…”
Section: The Amoebidiales and Eccrinales Are Not Fungimentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it was not surprising that nSSU rDNA analyses (Benny and O'Donnell, 2000;Ustinova et al, 2000) indicated that Amoebidium was located within the DRIP's clade (an acronym of the organisms included in this clade: Dermocystidium, rosette agent, Ichthyophonus, and Psorospermium), a recently proposed clade near the Animal-Fungi divergence (Ragan et al, 1996). The DRIP's clade was identified as a novel class Mesomycetozoea (Herr et al, 1999;Mendoza et al, 2002). Specifically, the nSSU rDNA data suggests that the closest relative of Amoebidium is the fish pathogen Ichthyophonus, but a specific phenetic connection between these two organisms has not been discovered.…”
Section: The Amoebidiales and Eccrinales Are Not Fungimentioning
confidence: 99%
“…This study also confirmed that the only other amoebidialean genus, Paramoebidium, is a sister group to Amoebidium. Currently, Mesomycetozoea contains two orders, the Dermocystidia and Ichthyophonida (Mendoza et al, 2002). These two orders are robustly supported as monophyletic, and the Amoebidiales-Eccrinales clade is indicated to be more closely related to the Ichthyophonida (Cafaro, 2005).…”
Section: The Amoebidiales and Eccrinales Are Not Fungimentioning
confidence: 99%
“…Both regions of 18S rRNA gene recover freshwater species, such as Amoebodium parasiticum or Anurofeca richardsi, even though they are parasites (Mendoza et al, 2002;Glockling et al, 2013). We also detected environmental ichthyosporeans.…”
Section: Diversity and Novelty Of Holozoamentioning
confidence: 79%
“…They constitute the most basic branch of the Animalia provisionally named the DRIP clade according to the first letters of its member genera (Dermocystidium, Ichthyophonus, Psorospermium and rosette agent) (EVANS and EDGERTON, 2002). There are some speculations that DRIPs belong to the class Mesomycetozoea with P. haeckeli belonging to its lowest order of Ichthyophonida (MENDOZA, TAYLOR and AJELLO, 2002). At present, two morphotypes of Psorospermium sporocysts can be distinguished in European astacid on the basis of size, morphology and histology: an ovoid morphotype which includes numerous globules of heterogeneous size and an elongated morphotype which contains smaller and homogeneous globules .…”
Section: Introductionmentioning
confidence: 99%